Personnel radiation dose assessment using a novel dosimeter in the department of radiology and dentistry in a medical facility in Delta State, South-South Nigeria: Our experience in the last 4 years - Omojola, Akintayo Daniel; Akpochafor, Michael Onoride; Adeneye, Samuel Olaolu; Aniekop, Ukeme Pius; Anizor, Margaret Idongesit; Ekpo, Mary-Ann Etim; Madu, Chibuzor Bede (The European Research Journal, 2018)
Objectives. Large percentages of X-ray facilities in Nigeria do not use radiation monitoring device; a few percentage that use them do not evaluate or carryout out assessment programs to ascertain the detriment to occupationally exposed workers. This study was aimed at evaluating dose reports from 2013 to 2016 for personnel who operate  radiation facilities and those that work within radiation field during certain X-ray procedures/examinations in the department of radiology and dentistry respectively; to ascertain if there is correlation between personnel dose and workload in both department and to determine if dose records are within acceptable limit recommended by the international atomic energy agency (IAEA) safety series.Methods. Direct ion storage (DIS) dosimeter was used for a total of 35 occupationally exposed personnel who work in the department of radiology and dentistry. The DIS dosimeter was read every two months and results were authomatically saved on the instadoseTM platform.Results. The mean (total) dose in radiology department for the first, second, third and fourth year was 0.17 ± 0.08 (3.52) mSv, 0.08 ± 0.03 (0.77) mSv, 0.07 ± 0.04 (0.72) mSv and 0.07 ± 0.05 (0.55) mSv and in Dentistry was 0.08 ± 0.02 (0.73) mSv, 0.05 ± 0.02 (0.42) mSv, 0.05 ± 0.02 (0.24) mSv and 0.07 ± 0.04 (0.34) mSv; respectively. There was significant difference in mean personnel dose from 2013-2016 in Radiology (p = 0.028) and in Dentistry Department (p = 0.004). Correlation of workload and personnel dose in Radiology (p = 0.240) and Dentistry Department (p = 0.765) wasn’t significant. There was no correlation in mean dose between both department (p = 0.256).Conclusion. Overall mean dose in both department for occupationally exposed personnel were below IAEA annual dose limit of 20 mSv averaged over a period of 5 consecutive years. Dose reports of personnel in both department reduced as the year progressed due to radiation safety awareness.